Social Media Analysis of High-Impact Information and Communication Journals: Adoption, Use, and Content Curation - Jesús Cascón-Katchadourian; Javier Guallar; Wileidys Artigas (Publications)
The use of social media to disseminate academic content is increasing, particularly in scientific journals. This study has the following two main objectives: first, exploring the use of social media by high-impact academic journals in two different SJR categories (Library and Information Sciences and Communication), and second, analyzing content curation carried out by the world’s most influential journals in both areas. The research methodology is descriptive with a quantitative approach regarding the items studied. The study finds that COM journals have a stronger social media presence than LIS journals, and X dominates in both categories and regions as the top social network, with significant influence as the only platform. On the other hand, content curation was found to a high degree in both areas, especially in the LIS area, with 93% vs. 80% in COM. The study highlights that both COM and LIS journals primarily focus on promoting recent articles, with COM diversifying content more than LIS. In terms of the content curation techniques used in both areas, the majority are abstracting and summarizing.